Winds of change in the midst of the storm - Mendoza Hernández, Liz Ena; León Suárez, Heidi Sulay; Barba Ortíz, Nidia Luz (Rastros Rostros, 2002)
Suddenly the sky blackened as if by magic and terrible winds began to blow in all directions; the ship called "SCHOOL", which in calm weather was huge and safe, became a small nutshell shaken violently by the dark waves.